Combined toxicity of polystyrene microplastics and perfluorobutane sulfonate on mouse liver: Impact on lipid metabolism and gut-liver axis disruption - Minghui Jiang; Xue Li; Chanjuan Cai; Yan Xu; Ping Song; Jing Yu (Ecotoxicology and Environmental Safety)
Microplastics (MPs) in the environment can adsorb perfluoroalkyl substance (PFAS), leading to combined toxicity in various organisms. Most researches have focused on single-exposure effects on mouse liver, with limited studies on the mechanisms behind the combined effects of polystyrene microplastics (PS-MPs) and perfluorobutane sulfonate (PFBS). This study analyzed the single and combined toxic effects of PS-MPs (10 mg/kg) and PFBS (30 mg/kg PFBSL or 300 mg/kg PFBSH) on mouse liver. Results indicated that PFBS was adsorbed by PS-MPs, affecting PFBS accumulation. Co-exposure significantly increased liver injury biomarkers in serum, associated with heightened oxidative stress, inflammation, and lipid accumulation. Metabolomics analyses revealed that the co-exposure had the most pronounced impact on lipid metabolism disorders, followed by PFBS and PS-MPs. Additionally, exposure to PS-MPs and PFBS induced gut microbiota dysbiosis and gut barrier disruption, disturbing lipid metabolism - particularly bile acids and short-chain fatty acids - along the gut-liver axis, thereby causing liver injury. Notably, co-exposure, particularly with high-concentration PFBS, significantly aggravated these effects. This study highlights the combined effects of PS-MPs and PFBS on liver function though lipid metabolism disorders and gut-liver axis imbalance, providing valuable insights into the health risks associated with these pollutants.